Advanced Endometrial Cancer Arising in Adenomyosis: A Case Report - Hiroaki NAGANO; Yuri FURUKAWA; Mariko UENO; Koichiro TAKAGI (Tokyo Women's Medical University Journal, 2018)
Endometrial cancer arising in adenomyosis (EC-AIA) is a rare form of uterine cancer. A 53-year-old Japanese postmenopausal female was referred to our outpatient clinic for adenomyosis. After the 4-year follow-up, she presented with an increased vaginal discharge. Endometrial curettage demonstrated either atypical endometrial hyperplasia or well-differentiated endometrioid carcinoma. Positron emission tomography/computed tomography revealed multiple pulmonary metastases, pelvic bone metastases, para-aortic node metastases, and uterine tumor as the primary lesion. She was clinically diagnosed with stage IVB endometrial cancer. Accordingly, total abdominal hysterectomy and bilateral salpingo-oophorectomy were performed. Macroscopic findings of the resected uterus were difficult to distinguish from ordinal adenomyosis. Microscopically, diffuse endometrioid carcinoma (grade 2) occupied the entire uterine body, coexisting with adenomyosis. Postoperatively, chemotherapy and zoledronic acid administration were initiated, which are ongoing till date. The case highlights that EC-AIA, a rare but aggressive disease, should be considered when managing patients with adenomyosis.